What instruments are available to aid or evaluate personalised care delivery, from the perspectives of healthcare practitioners and service users? A narrative scoping review. - Louise Johnson; Beth Clark; Lyndsay Court; Hayden Kirk; Matthew Wood; Sharon Jackson; Mari Carmen Portillo (PLoS ONE)
Background Although the widespread implementation of personalised care is commonly cited as one of the solutions to managing the burden of increasing multimorbidity, there is no established method for assessing and evaluating personalised care delivery. This review sought to describe the range of existing tools, instruments or methods for assessing, evaluating or measuring personalised care delivery, from the perspectives of healthcare practitioners and/or service users. Methods A scoping review of literature published since 1990. Results From 3851 potential citations, 172 were included. Of these, 103 reported the development of a new instrument, and 69 reported the adaption of an existing instrument. Most instruments (81%) were designed for use in a specific clinical population. A focus on supported self-management was particularly common (80%). Few instruments were identified that explored the views of healthcare staff (n = 8) or carers (n = 1). Content analysis generated six domains: understanding the person; understanding capability; understanding behaviour; personalised care interventions; experience of care; and wider determinants. These domains have been used to propose a concept framework. Conclusion This review identified a high number of instruments, designed to support personalised care delivery or evaluation. Many were designed to understand a single construct of care (e.g., supported self-management), at an individual level (e.g., patients) and in a specific population (e.g., diabetes). For clinicians wishing to utilise a standardised instrument for a specific purpose, there are many to choose from. Yet no tools encompass the full spectrum of constructs encapsulated within personalised care. Future work should focus on how instruments are used to improve personalised care delivery, particularly through a less siloed, multimorbidity lens.